Licensed practical nurses professionals: ten year salary time series (Research, Society and Development, 2021)
The Brazilian nursery has been fighting for professional recognition, a more humane workload and a fairer salary policy. In this context, mid-level nursing professionals are also included. The objective of this study was to analyze a time series of salaries of nursing assistants and technicians in their first job, from 2010 to 2019. A retrospective epidemiological study was carried out with graduates of a nursing technician course from the federal education network from 2010 to 2019. The 143 graduates were included, most of them young women. The average remuneration was R$1,702.92 (minimum of R$790.00 and maximum of R$4,000.00). The wage time series is a constant trend in the period analyzed, while the minimum wage has an increasing trend. The remuneration of nursing technicians/auxiliaries is below what the professional category wants. The existence of a bill that determines the category's wage floor and a working day is in line with the valuation of working workers; and its implementation as a public policy tends to strengthen this collective. The salary stagnation evidenced in the time series may represent a risk of professional evasion for other types of work.